Techniques to measure cocirculation and cross-border movement of currency - Krueger,Russell ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1997)
Examines methofologies to measure cross-border flows of currnecy and use of foreign currencies within an economy. Discusses policy implications of co-circulation, regarding exchange rate policy, seigniorage, inflation control, and international integration of monetary systems, and currency management.